Answer:
a) Tb = m (g + vb² / R) , b) Tt = m (g - vt² /R), c) Tb = Ty + (vb² -vt²) /R
Explanation:
a) For this exercise we will use Newton's second law, at the bottom
Tb - W = m a
Where the acceleration is centripetal
a = v² / R
Tb = W + m vb² / r
Tb = m (g + vb² / R)
b) the tension at the top
-Tt -w = m a
Tt = W - m vt² / R
Tt = m (g - vt² / R)
c) write the two equations and solve system
Tb = m (g + vb² / R)
Tt = m (g - vt² / R) (-1)
We multiply by (1) and add
Tb -Ty = vb² /R -vt² /R
Tb = Ty + (vb² -vt²) / R